Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T01:02:20+01:00
Funkcja liniowa f określona jest wzorem f(x) = ax+b
1) dla f(f(f(0)))=1 mamy
f(0) = a*0+b = b
f(f(0)) = f(b) = a*b+ b =ab+ b
f(f(f(0))) = f(f(b)) = f(ab+b) = a*(ab+b)+b = a²b+ ab+ b
czyli a²b+ ab+ b = 1
2) dla f(f(f(1)))=3
f(1) = a*1+ b = a+ b
f(f(1)) = f(a+ b)= a*(a+ b)+ b= a²+ ab+ b
f(f(f(1))) = f(f(a+b)) = f(a²+ ab+ b)= a*(a²+ ab+ b)+ b=
a³+ a²b+ ab+ b
czyli a³+ a²b+ ab+ b = 3 {za wyrażenie a²b+ ab+ b wstawiamy 1}
a³+ 1 = 3, stąd a³= 2
3) Obliczamy f(f(f(1002)))
f(1002) = a*1002+ b = 1002a+ b
f(f(1002)) = f(1002a+ b) = a*(1002a+ b)+ b = 1002a²+ ab+ b
f(f(f(1002))) = f(f(1002a+ b)) = f(1002a²+ ab+ b)=
a*(1002a²+ ab+ b)+ b = 1002a³+ a²b+ ab+ b
{za a³wstawiamy 2, a za wyrażenie a²b+ ab+ b wstawiamy 1}
f(f(f(1002))) = 1002a³+ a²b+ ab+ b = 1002*2 + 1 = 2004+ 1 = 2005
Odp. f(f(f(1002)))= 2005



1 5 1